CHANGES IN MACULAR THICKNESS AND VISUAL ACUITY AFTER INTRAVITREAL BEVACIZUMAB INJECTION IN PATIENTS WITH RETINAL VEIN OCCLUSION: Macular Thickness and Visual Acuity - Qureshi, Naveed Ahmed; Zafar, Sarah A; Khalid, Muhammad Kamran; Qureshi, Nadeem; Ambreen, Fareeha (Pakistan Armed Forces Medical Journal, 2014)
Objective: To evaluate the effect of single Intravitreal Bevacizumab (Avastin) injection on visual acuity (VA) and central retinal thickness (CRT) in patients with macular edema secondary to branch retinal vein occlusion (BRVO) or central retinal vein occlusion (CRVO). Study Design: Prospective, non-randomized, interventional case series. Place and Duration of Study: This study was conducted at Al-Shifa Trust Eye Hospital Rawalpindi from March 2012 to February 2013. Patients and Methods: Twenty three patients with macular edema attributable to vein occlusion received intravitreal injection of Bevacizumab 1.25 mg. Nine patients had central retinal vein occlusion (CRVO) and 14 patients had branch retinal vein occlusion (BRVO). Complete ophthalmic examination including best corrected visual acuity (BCVA) and optical coherence tomography (OCT) was done at base line and follow up visits. Results: At base line mean visual acuity was Log MAR 0.73 and showed improvement to mean Log MAR 0.39 at 12 weeks after intravitreal Bevacizumab (IVB) injection. Mean CRT was 527 μm at baseline that decreased to 274 μm after 12 weeks of IVB treatment. Conclusion: Intravitreal Bevacizumab appears to result in significant short term improvement of VA and macular edema secondary to vein occlusion.